O conceito de lucro econômico no âmbito da contabilidade aplicada - Fuji, Alessandra Hirano (Revista Contabilidade & Finanças, 2004)
The study of accounting theory and the definitions of financial elements, especially profit, is highly relevant not only for academics, but also for those directly involved in practical activities related to applied accounting. Accounting profit is the confrontation between revenue and cost and is based on conservatism, objectivity and Generally Accepted Accounting Principles. Economic profit is the increase in the equity's present value and involves subjective aspects, but it is better than accounting profit, mainly in the context of internal and external users' decisionmaking process. The research question is whether the concept of economic profit is really widespread among accounting professionals. This study aims to emphasize the importance of economic profit concept and to verify how this concept is assimilated, used and disclosed in the context of applied accounting. Based on a literature review and an exploratory study, this research shows that the concept of economic profit is not fully known and used by accounting users.